Computational chemistry-assisted design of a non-fullerene acceptor enables 17.4% efficiency in high-boiling-point solvent processed binary organic solar cells. Issue 39 (20th September 2022) - Cai, Guilong; Chen, Zeng; Li, Tengfei; Xia, Xinxin; Fu, Yuang; Xu, Luhang; Chi, Weijie; Zhang, Jianqi; Zhu, Haiming; Zhan, Xiaowei; Lu, Xinhui
Abstract : A new non-fullerene acceptor, namely BOEH-4Cl, was computational chemistry-assisted designed and synthesized. Paired with polymer donor PM6, the high-boiling-point solvent processed binary BOEH-4Cl-based OSCs exhibit a best efficiency of 17.4%. Abstract : Designing new high-performance non-fullerene acceptors is the key driving force for the development of organic solar cells (OSCs). In this work, a new acceptor, BOEH-4Cl, was designed based on the end-group chlorination of L8-BO. Theoretical calculations successfully predicted the expected experimental results based on the optoelectronic properties of BOEH-4Cl and L8-BO and intermolecular interaction of PM6/BOEH-4Cl or L8-BO. A high-boiling-point solvent (HBPS, chlorobenzene) was also introduced as a calculation factor, which is beneficial to future industrialization. In agreement with the calculated results, the optimized HBPS-processed BOEH-4Cl film exhibited tighter molecular packing, a more efficient interfacial hole transfer process and lower non-radiative energy loss, demonstrating necessary properties as a promising acceptor. The efficiency of optimized HBPS-processed PM6/BOEH-4Cl OSCs reached 17.4%, much higher than that of PM6/L8-BO (14.5%). Hence, this work demonstrates the great potential of utilizing theoretical chemical calculations to assist in the design of acceptor molecules to reduce time and cost.